Pandemics and Intergenerational Mobility of Education: Evidence from the 2003 Severe Acute Respiratory Syndrome (SARS) Epidemic in China - Wenquan Liang; Sen Xue (Global Labor Organization (GLO), 2021)
This paper examines the impact of the SARS epidemic in 2003 on intergenerational mobility in China. Using large cross-city variation in SARS cases, our triple difference-in-differences estimates suggest that the SARS epidemic significantly increases the intergenerational transmission of education. Our results show that a one percent increase in the number of SARS cases leads to a 9.3 percent increase in the maternal intergeneration transmission coefficient. The effect of the SARS epidemic is stronger for admission to 4-year bachelor programmes and more concentrated in female students and students in large cities. This paper also investigates the potential mechanisms and finds that more highly educated mothers tend to be more engaged in children's studies during the epidemic period when teachers are absent. These results convey the warning message that pandemics may reduce intergenerational mobility of education
Keywords: I24; I18; J62; 330; Pandemic; Epidemic; intergenerational mobility; SARS